PENINGKATAN KEMAMPUAN MOTORIK HALUS DENGAN MENGGUNAKAN KEGIATAN KIRIGAMI PADA SISWA CEREBRAL PALSY KELAS III DI SLB NEGERI 1 MAROS - Suci Afianti Ramadhani; Tatiana Meidina; Usman Usman (JURNAL ORTO DIDAKTIKA, 2024)
This study examines fine motor skills in spastic type cerebral palsy students by providing kirigami activities as a stimulus to train movements on stiff fingers at SLB Negeri 1 Maros. The problem formulations of this research are: (1) What is the description of the improvement of fine motor skills before the application of kirigami activities in cerebral palsy students. (2) What is the description of the improvement of fine motor skills after the application of kirigami activities for cerebral palsy students. (3) Is there an effect of kirigami activities on improving fine motor skills in cerebral palsy students. The objectives of this study are: (1) To determine fine motor skills before the application of kirigami activities in cerebral palsy students. (2) To determine fine motor skills after the application of kirigami activities in cerebral palsy students. (3) To determine whether there is an effect of kirigami activities on improving fine motor skills in cerebral palsy students. This research approach is quantitative research with descriptive research type. With Kirigami Activities can increase Fine Motor Skills in Cerebral Palsy Students. The data obtained were analyzed through descriptive statistics and displayed graphs. The results of the study concluded that there was an effect of Kirigami activities on improving fine motor skills in cerebral palsy students in Class III at SLB Negeri 1 Maros.